Use Multimedia Tools to Solve Simple Issues in Primary Education - Kattayeva Feruza Bachranovna (Zien Journals, 2022)
The articlecontains meto dological content, which emphasizes the methodological characteristics of explaining the solution of soda issues in primary education using multimedia tools.
Keywords: Simple Issue; Multimedia; presentation; complex issue